Bioprinting of 3D in vitro skeletal muscle models : a review - Zhuang, Pei (2021)
Recent years have witnessed significant progress in skeletal muscle tissue regeneration. Numerous bioengineering approaches have been implemented to construct in vitro skeletal muscle tissues with high fidelity. Nevertheless, an in vitro model that is capable of restoring mature muscle, vasculature, and ECM composition to the damaged tissue has yet to be achieved. Herein, we critically review the development and progress in tissue engineering skeletal muscle models. We outline the physiology of native skeletal muscle and the design criteria of engineering biomimetic skeletal muscle tissues are discussed. The influential parameters that modulating skeletal muscle cell behavior are highlighted. Subsequently, we critically review the 3D skeletal muscle models using various bioengineering strategies, including 3D geometrical confinement, electrospinning, porous hydrogels, the controlled cell/molecule delivery, and particularly, 3D bioprinting technology. We draw on specific examples to discuss the merits and limitations of each method. A short description of the challenges and future directions is provided.